2019
DOI: 10.3389/fevo.2019.00202
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Dimensionality Scales Up to Generate Bimodal Consumer-Resource Size-Ratio Distributions in Ecological Communities

Abstract: Understanding constraints on consumer-resource body size-ratios is fundamentally important from both ecological and evolutionary perspectives. By analyzing data on 4,685 consumer-resource interactions from nine ecological communities, we show that in spatially complex environments-where consumers can forage in both two (2D, e.g., benthic zones) and three (3D, e.g., pelagic zones) spatial dimensions-the resource-to-consumer body size-ratio distribution tends toward bimodality, with different median 2D and 3D pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…For instance, the scaling of the attack rate with predator and prey body masses strongly determines the occurrence of limit cycles (Pawar et al, 2019) and varies a lot between studies (Rall et al, 2008;Pawar et al, 2012). However, such differences do not change our main results as the C and SC models respond similarly whatever the values of our scaling constants ( Fig.…”
Section: Paradox Of Enrichment In Our Food Web Modelmentioning
confidence: 75%
“…For instance, the scaling of the attack rate with predator and prey body masses strongly determines the occurrence of limit cycles (Pawar et al, 2019) and varies a lot between studies (Rall et al, 2008;Pawar et al, 2012). However, such differences do not change our main results as the C and SC models respond similarly whatever the values of our scaling constants ( Fig.…”
Section: Paradox Of Enrichment In Our Food Web Modelmentioning
confidence: 75%
“…For such applications, it may useful to turn to the marine literature where development of SDM techniques for 3‐D systems is already underway (e.g., Duffy & Chown, 2017; Pérez‐Costas et al, 2019). Similarly, investigations into the scaling of interaction strengths within species networks can differ between 2‐ and 3‐D systems in terrestrial and marine realms, where advanced nonlinear statistical approaches, 3‐D statistical point pattern models and 3‐D agent‐based modelling have been successfully applied (see Barrios‐O’Neill et al, 2016; Pawar, Dell, Lin, Wieczynski, & Savage, 2019; Raynaud & Nunan, 2014).…”
Section: Spatio‐temporal Considerationsmentioning
confidence: 99%
“…2019) and consumption rate (Pawar et al. 2012, 2019) should have on the scaling of diet quality. In termites, metabolic divergence between mandible types is clear (Pequeno et al.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it has been suggested that the dimensionality of foraging space (2D or 3D) drives the scaling of consumption rate (Pawar et al. 2012, 2019), but this is based on unrealistic assumptions about metabolic scaling (Harrison 2017; Glazier 2018). Thus, the precise links between body size, physiological rates, and diet quality require further study.…”
Section: Discussionmentioning
confidence: 99%